The labor market value to legal status - Fernando A. Lozano; Todd Sorensen (Institute for the Study of Labor (IZA), 2011)
We present estimates of the effect of legal immigration status on earnings of undocumented workers. Our contribution to the literature centers on a two-step procedure that allows us to first estimate the legal status of an immigrant and then estimate the effect of the Immigration Reform and Control Act (IRCA) on immigrants' labor market outcomes using a triple difference approach. From a sample of young to middle aged Mexican men, our results show that IRCA causes a 20 log point increase in labor market earnings of Mexican immigrants over the long run, and that nearly all of this increase is in the occupational wage. These results suggest that the primary disadvantage for undocumented workers is the type of jobs that they are able to obtain. We estimate the model for immigrants from other countries not benefiting from IRCA to the extent that Mexican immigrants did, and find no systematic bias towards positive and significant results.
urn:nbn:de:101:1-201104113655
Keywords: J08; F22; 330; immigration; legal status; immigration reform; Migranten; Einwanderungsrecht; Reform; Wirkungsanalyse; Lohn; Mexikaner; USA